HOUSEHOLDS IN ROMANIA AND THEIR RELATION WITH THE ECONOMIC GROWTH: STUDY CASE FOR 2010-2016 - Corina CRUCERU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Household are in a manner of speaking small motors for a national economy and for the consumption in particular. In most cases, the way a household is managed and its basic characteristics can reflect the economic processes that occur in a specific moment in the financial and economic context and are a great measurement unit for the real standard of living within a country. In this paper we will present the main characteristics of the household in Romania between 2010-2016 and its relation with the given economic growth indicators.